(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
In this study, abundant ginseng leaf saponins were converted into minor ginsenosides that havemore pharmacological efficacy via fermentation process using recombinant β-glucosidase (bgp1). This fermented product was used to investigate the stimulatory effect on differentiation and mineralization of murine osteoblastic MC3T3-E1 cells. All major ginsenosides which areavailable in ginseng leaf were biotransformed into more pharmacologically active minor ginsenosides within a short time of incubation. The results showed that 100% of ginsenoside Rd, Rg1and Re were decomposed and transformed to Rg3, Rh1and Rg2, respectively within 03 (three) hours of incubation. Ginseng leaf saponin contains 17.1% Rg1, 44.9% Re, 10.8% Rd, 4.8% Rb1, 5.7% Rb2, 6.9% Rc,2.7% Rg2, and 6.8% F1 ginsenoside. But after fermentation, the products contain mostly pharmacological active minor ginsenosides including 42.2% Rg2, 13.7% Rg3, 8.8% Rh1, 4.9% F1 and 3.6% PPT ginsenosides. Moreover, we investigated and compared the effect of leaf saponins (LS) and fermented leaf saponins (FLS), on the differentiation and mineralization of pre-osteoblastic MC3T3-E1 cells. Treatment with FLS remarkably enhanced cell viability in a dose-dependent manner. FLS notably stimulated the ALP activity, Coll-I synthesis and mineralization ability of MC3T3-E1 cells. Based on the comparison between LS and FLS, it is clear that FLS has good effect on differentiation of osteoblastic MC3T3-E1 cells and bone formation. Therefore, bgp1-fermented ginseng leaf saponins could be a novel treatment for osteoporosis prevention. Bangladesh J. Sci. Ind. Res.54(2), 147-154, 2019